The effective control of Cu through-silicon via extrusion for three-dimensional integrated circuits by a metallic cap layer. (15th April 2019) - Jalilvand, Golareh; Ahmed, Omar; Spinella, Laura; Zhou, Le; Jiang, Tengfei
Abstract: This work demonstrated a new and promising approach to control via extrusion for three-dimensional integrated circuits (3DICs). By depositing 50 nm of Ta as a metallic cap, a significant reduction in both the magnitude and the statistical spread of extrusion was achieved. Thermo-mechanical and interfacial characterization were further carried out to study the mechanism of the observed effect. The results suggested that the Ta cap layer was able to effectively suppress the mass transport at via top surface and along grain boundaries, therefore reducing extrusion. Graphical abstract: Unlabelled Image